A Rare and Fatal Case of Cutaneous T-Cell Lymphoma (CTCL) - Lia Sasmithae; Indra Perdana (National Cancer Center - Dharmais Cancer Hospital, 2021)
Introduction: Cutaneous T-Cell Lymphoma (CTCL) is a form of Non-Hodgkin Lymphoma involving T-cell neoplasms mainly concentrated in the skin. Primary Cutaneous Peripheral T-Cell Lymphoma is Not Otherwise Specified (PTL-NOS) is the rarest case of CTCL disease.Case Presentation: A female, 35 years old, complained of a lump on her face. In the last 3 months, the lump felt soft, contained a liquid that, when it ruptures, secretes Blood, and the crusty scar will blacken and easily bleed with pain. Physical examination of pale conjunctiva on the face, neck, chest, abdomen, back, and legs obtained nodules with a chewy consistency with erythema appearance in varying size. Some nodules that appear were covered in blackish crustae. The right lung has a decrease in the sound of breath, accompanied by swelling in both limbs. The conclusion of bilateral femur skin biopsy impresses cutaneous T lymphoma cells. Within three months, cancer developed into lesions spread almost throughout the body, and due to the rapid and progressive nature of cancer, its diagnosis developed into PTL-NOS.Conclusions: Patients with PTL-NOS may come with solitary nodules such as red tumors in any area of the body. However, most often, patients come with symptoms of multifocal or diffuse scattered nodules. In enforcing the diagnosis, it takes a high level of suspicion, and multiple rebiopsies are necessary to enforce the diagnosis of CTCL.